KEDUDUKAN DOKTRIN RES IPSA LOQUITUR (DOKTRIN YANG MEMIHAK PADA KORBAN) DALAM TATA HUKUM INDONESIA - APRIANI, TITIN (GANEC SWARA, 2020)
This research is a library research that uses data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is by collecting various ideas, theories and concepts from various literatures that focus on the process of comparison between the arguments or other laws. The results of the study can be drawn a conclusion that the doctrine of res ipsa loquitur can be applied in Indonesia through the evidences that have been concluded by the judge, in accordance with applicable law. Article 173 of the RIB states that the allegations which are not based on an applicable law, may only be considered by the judge in passing the verdict, if the allegations are important, thorough, certain and in accordance with one another. In line with Article 1922 of the Civil Code, it is stated that the allegations that are not based on the law are left to the consideration and alertness of judges, which should not be considered by other allegations, other than those that are thorough and certain, and in accordance with each other